Performance of eco-friendly polymers for soil stabilization and their resistance to freeze–thaw action. (23rd May 2023) - Bozyigit, Irem; Zingil, Hande Ozenc; Altun, Selim
Abstract: Soil improvement methods using environmentally friendly additives have gained popularity with increased environmental awareness. In the future, environmentally friendly polymers can be preferred in the stabilization of many geotechnical applications like the base of roads, landfills, and sub-base of foundations. This means the mechanical properties of these eco-friendly polymers should be investigated in detail. For this purpose, changes in the mechanical properties of specimens treated with different polymer types under freeze–thaw action were investigated. Three types of polymers which are xanthan gum, guar gum, and anionic polyacrylamide polymer were used to improve the strength properties of kaolin clay. The specimens were prepared in 3 different anionic polymer contents and 4 different biopolymer content. After 7, 14, and 28-day curing periods specimens were subjected to 5 and 10 cycles of freezing–thawing to observe freeze–thaw action by conducting unconfined compression tests and the control specimens were directly subjected to unconfined compression tests after the curing period. Regarding the outcomes obtained, both synthetic and biological polymer use induced strength gain. Guar gum which is a biological polymer is the most effective that improves the strength by around 8 times than pure clay. This increment ratio varied between 2 and 3.5 times in polyacrylamide polymer, which is a greater strength increase than in previous studies. In addition, curing time has no significant effect on strength gain in anionic polyacrylamide-contained specimens. It was also observed that freezing–thawing caused a drastic reduction in strength by around 5 to 60%, however, the anionic polymer is the most resistant to freeze–thaw considering the strength loss. As a result, eco-friendly polymers are suitable in regions exposed to freeze–thaw action between the seasons. Graphical abstract: Highlights: The efficiency of polyacrylamide polymer (PAM), guar gum and xanthan gum was compared. Guar gum stabilization induced the greatest increase in strength. PAM is the most resistant to freeze–thaw considering the strength loss. Guar gum is more effective than xanthan gum and PAM under freezing-thawing. Microscopic interactions between clay and polymers were investigated.